Tax collection in Algeria - Bareche, Aissa; Beliman, Yamina (Journal of Human Sciences, 2021)
The tax collection is the last and most important stage of the tax process as a whole, as it is the ultimate coronation of several stages, and it results in providing the public treasury with the funds necessary to achieve development in various fields. Tax collection in Algeria remained weak for several reasons, including the lack of interest in it by the guardians, due to the presence of petroleum collection that covers the existing financial deficit, as well as the use of rudimentary methods of collection, especially with the spread of what is known as electronic management, which enables to achieve an increase in collection whether at the central or central level, which the Algerian governments are trying to materialize in reality, and this is what we will study in this research paper.